1995
DOI: 10.2105/ajph.85.8_pt_1.1109
|View full text |Cite
|
Sign up to set email alerts
|

Form of day care and respiratory infections among Finnish children.

Abstract: The relationship between respiratory infectious diseases and form of day care was assessed in a retrospective cohort study of 2568 randomly selected children aged 1 through 7 years in Espoo, Finland. Day-care center children had an increased risk for the common cold, acute otitis media, and pneumonia. The risk concentrated in 1-year-old children, for whom the adjusted relative risks (incidence density ratios) for the common cold, otitis media, and pneumonia were 1.69 (95% confidence interval [CI] = 1.43, 2.01)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
77
0
14

Year Published

1999
1999
2011
2011

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 139 publications
(94 citation statements)
references
References 17 publications
3
77
0
14
Order By: Relevance
“…The decision was made to investigate noninstitutionalized infants because viral and bacterial infections are rapidly disseminated in day care centers and could affect the frequency of signs and symptoms. 15,16 Moreover, a previous study conducted in Brazil found that, at public and private day care centers, the proportion of caregivers to children aged 0 to 2 years is 1:6 and 1:9, respectively, 17 which could have a negative effect on the validity and reliability of the data. The aim of assessing the day before and after tooth eruption was based on previous studies reporting that infants exhibit signs and symptoms on days surrounding the day of eruption that may be associated with teething.…”
Section: Discussionmentioning
confidence: 99%
“…The decision was made to investigate noninstitutionalized infants because viral and bacterial infections are rapidly disseminated in day care centers and could affect the frequency of signs and symptoms. 15,16 Moreover, a previous study conducted in Brazil found that, at public and private day care centers, the proportion of caregivers to children aged 0 to 2 years is 1:6 and 1:9, respectively, 17 which could have a negative effect on the validity and reliability of the data. The aim of assessing the day before and after tooth eruption was based on previous studies reporting that infants exhibit signs and symptoms on days surrounding the day of eruption that may be associated with teething.…”
Section: Discussionmentioning
confidence: 99%
“…All the studies 6,7,10,19,23,27,33,34 but two 4,12 found an increased risk of URI among children attending childcare centers. Despite the variety of methods used, the relative risks reported did not vary widely, most studies reporting a relative risk below two.…”
Section: Child-care Attendance and Child Morbidity Upper Respiratory mentioning
confidence: 95%
“…Two one-year historical cohort studies were conducted in Scandinavia by Petersson et al 27 and Louhiala et al 23 . In one study 27 , morbidity information of children aged 1-3 years was collected from medical records, and attendance at child-care centers and child-care homes was informed by the local authority.…”
Section: Child-care Attendance and Child Morbidity Upper Respiratory mentioning
confidence: 99%
See 2 more Smart Citations